S7A:8 Efficacy and safety of ustekinumab, an interleukin 12/23 inhibitor, in patients with active systemic lupus erythematosus: results of a phase 2, randomised placebo-controlled study. (21st March 2018) - van Vollenhoven, R; Hahn, B; Tsokos, G; Wagner, C; Lipsky, P; Hsu, B; Chevrier, M; Gordon, R; Triebel, M; Rose, S
Abstract : Purpose: IL12 and IL23 pathway have been linked to SLE pathogenesis. Anti-IL12/23 monoclonal antibody ustekinumab (UST) previously approved for psoriasis, psoriatic arthritis, and Crohn's diseasewas evaluated in pts with active SLE. Methods: A Ph2, PBO-controlled study in 102 adults with seropositive SLE by SLICC criteria with active disease despite standard-of-care therapy were randomised to UST vs PBO, added to standard care. Primary endpoint was the proportion achieving SLE response index (SRI)−4 response at wk24. Secondary endpoints included change SLEDAI-2K, Physician's Global Assessment (PGA), and BICLA response. Results: The mITT population (includes pts who received at least one dose) at wk24 revealed 60% of UST pts with SRI-4 response vs 31% in PBO (p=0.0046). Pts in UST group had greater median change from wk0 to wk24 in SLEDAI-2K and PGA vs PBO (table 1). No difference was observed in BICLA composite response at wk24, but more UST pts had no BILAG worsening vs PBO. Through wk24, 78% of UST pts and 67% of PBO pts had greater than or equal to 1 AE; 8.3%–9.5%, respectively, had greater than or equal to 1 SAE (table 1). There were no deaths in the study. Safety events were consistent with UST safety profile in other studied indications. Conclusion: UST showed efficacy in treatment of active SLE vs PBO and comparable safety warranting further investigation. UST may work via a novel mechanism of action in SLE.